(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Teacher has to play a vital role in the development of desirableattitude, beliefs and values among the students. The teacher’s role is not onlyconfined to mere transmission of knowledge and transaction of prescribedcurriculum but also to perform many other roles such as the role of afacilitator, guide and counsellor; manager of classroom situation; innovatorand researcher; planner, organiser and implementer of educational activities,schemes and programmes; promoter of socio-moral values; evaluator ofachievements made by the pupils; social reformer and modifier of humanbehaviour; contributor in achieving the national goals; implementer ofprescribed curriculum and learning specific curriculum developed for specialneed children. Teachers have todischarge all these functions effectively, therefore teachers own perspective,their skills and abilities and competence must be fully developed so that theymay be committed to their learners and teaching profession as well as to thesociety.